Circular Solutions for Decent Work and Economic Growth: Lessons from Sustainable Development Goals (SDG) 8: Solusi Sirkuler untuk Pekerjaan yang Layak dan Pertumbuhan Ekonomi: Pelajaran dari Sustainable Development Goals (SDG) Nomor 8 - Sri Kurnia; Muhammad Isa Alamsyahbana; Rachmad Chartady; Surya Violita Arifin; Mohammad Iqbal Sesaria (Universitas Muhammadiyah Sidoarjo, 2023)
The purpose of this research is to provide information about circular solutions for decent work economic growth which includes lessons from SDG 8. However, the circular economy is a promising approach to achieving sustainable development, by decoupling ecomonic growth from resource depletion and environmental degradation. The circular economy can support the achievement of multiple SDGs, by promoting sustainable and inclusive economic growth, reducing waste and pollution, and fostering innovation and resilience. The circular economy has the potential to contribute to SDG 8 by creating new job opportunities, promoting skills development and innovation, also it can fostering sustainable and inclusive economic growth. By adopting circular practices, businesses and governments can create new value and reduce their environmental impact, while promoting social and economic development. Highlights: The circular economy offers a promising approach to achieving sustainable development by decoupling economic growth from resource depletion and environmental degradation. Circular practices can contribute to SDG 8 by creating new job opportunities, promoting skills development, and fostering sustainable and inclusive economic growth. By adopting circular solutions, businesses and governments can create new value, reduce environmental impact, and drive social and economic development. Keywords: Circular solutions, Decent work, Economic growth, Sustainable development goals (SDGs), Resource efficiency